Determinants Of Economic Growth In Central Java 2018 - 2023 - Sholikhah, Anna Uswatun; Deden Dinar Iskandar (Finance : International Journal of Management Finance, 2024)
The economy of a region is assessed based on its economic growth, which is a measure of the success of development in the region. Economic growth is a long-term increase in per capita production that reflects the dynamics of the economy. Evaluating economic growth is an important metric to assess the progress of a region, where the economy of a region will be better if its economic growth is faster. This study aims to analyze four factors that influence economic growth, namely: 1) the influence of the labor force, 2) the influence of years of schooling, 3) the influence of population density, and 4) the influence of the Human Development Index (HDI). This research is a quantitative study using secondary data from BPS for the period 2018-2023 and panel data regression analysis with Eviews 12. The results showed that: 1) the labor force has a significant positive effect on economic growth, 2) length of schooling has a significant positive effect on economic growth, 3) population density has a significant negative effect on economic growth, and 4) HDI has a significant positive effect on economic growth.